(untitled) (African Journal of Biomedical Research, 2024)
The emergence of canine parvovirus (CPV) in 1978, probably as a result of the cross-species incursion of feline panleukopenia virus, resulted in the current pandemic of canine parvoviral enteritis. It has been 40 years since the virus was first identified in Nigeria and it has been afflicting dog population in the country unabatedly. As such, in this review, CPV molecular epidemiology in Nigeria entailing its prevalence, occurrence of subtypes, co-infection and genetic evolution are analysed. All the three subtypes of the virus have been identified in the country with CPV-2a subtype being preponderant. However, in recent years there has been an upsurge in the number of CPV-2c and it is often associated with bloody diarrhoea even in vaccinated puppies. Therefore, there is need for proper assessment of the molecular epidemiology of the virus for proper institution of effective control policies to eradicate this pathogen